1989
DOI: 10.1002/chin.198951025
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Crystalline Holmium Dichloride.

Abstract: The solid phase reaction between HoCl3 and Ho, which is conducted at 780 K under a vacuum, affords the title compound, whose structure is elucidated by XRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Our molar enthalpy results for this transition, trs H m , as well as temperature and enthalpy of fusion, fus H m , agree well with Dworkin and Bredig data [15]. The enthalpy data given by Goryushkin et al [29] are significantly higher, but they were obtained by a DTA comparative method.…”
Section: Temperatures and Enthalpies Of Phase Transitions Of Lanthanisupporting
confidence: 85%
“…Our molar enthalpy results for this transition, trs H m , as well as temperature and enthalpy of fusion, fus H m , agree well with Dworkin and Bredig data [15]. The enthalpy data given by Goryushkin et al [29] are significantly higher, but they were obtained by a DTA comparative method.…”
Section: Temperatures and Enthalpies Of Phase Transitions Of Lanthanisupporting
confidence: 85%
“…It was shown [13] that solid dysprosium trichloride forms the PuBr 3 type structure only at elevated temperatures and pressures (e.g., 520 °C and 40,000 atm), whereas at normal pressure and the same temperature, DyCl 3 has a thermodynamically stable monoclinic structure of the AlCl 3 type. The absence of any phase transitions in solid DyCl 3 was recognised from the results of many DTA and XAFS studies [14][15][16][17][18]. The authors of the much used Handbook on the properties of rare earth halides [19] are forced to note the essential disagreements between the results of different researchers; therefore, to date, the reasons for the conflicting data on the existence or absence of DyCl 3 polymorphism are not established.…”
Section: Introductionmentioning
confidence: 98%
“…It is of interest that the terbium trichloride dividing these two salt groups has an orthorhombic crystalline lattice (PuBr 3 type, D 2h 17 , Z = 4, CN = 8) which is extrinsic to other lanthanide trichlorides. It is found that TbCl 3 is thermally unstable and undergoes the phase transition at 510 °C [3] from orthorhombic structure to tetragonal one (D 4h 14 , Z = 2, CN = 6).…”
Section: Introductionmentioning
confidence: 99%
“…In this case one of the problems is the determination of the lanthanides ions oxidation state in molten electrolytes. It is well-known [6,[32][33][34][35][36][37][38] that the stable valent states of thulium and ytterbium are di-and trivalent ions. That's why we can expect that the redox reactions in studied systems will be single-electron reaction.…”
Section: Introductionmentioning
confidence: 99%